Complex physical rehabilitation of children at bronchial asthma of II of the stage of weight on the stationary stage - Пєшкова [Olga Peshkova], Ольга Володимирівна; Авраменко [Olga Аvramenko], Ольга Миколаївна; Мітько [O. Mitko], О. В.; Третяк [L. Tretyak], Л. О. (Slobozhanskyi Herald of Science and Sport, 2013)
In the article by authors had been represented a program of physical rehabilitation, worked out for children 13–15 years, suffering by persistent bronchial asthma of II of the stage of weight which was used on the stationary stage of restoration treatment. This program included a medical gymnastics with the use of respiratory exercises with the elements of the general and local muscular weakening, nasal breathing, massotherapy, physiotherapy, autogenic training and hardenings procedures. Efficiency of this program is well-proven on the basis of study of dynamics of indexes of the functional state of the respiratory and cardiovascular system at the inspected contingent of patients.